Characteristics and health‐status outcomes in patients with atrial fibrillation detected via health screening. Issue 1 (27th October 2022) - Yamashita, Terumasa; Kimura, Takehiro; Ikemura, Nobuhiro; Niimi, Nozomi; Tsuzuki, Ippei; Seki, Yuta; Ibe, Susumu; Hashimoto, Kenji; Miyama, Hiroshi; Fujisawa, Taishi; Katsumata, Yoshinori; Tanimoto, Kojiro; et al.
Abstract: Background: Early detection of atrial fibrillation (AF) is important. Japan has a universal screening system, and regular health screening (HS) is available to support AF detection without a hospital visit. However, health‐related outcomes and other characteristics of HS‐detected and conventionally diagnosed AF remain unknown. Hypothesis: That the characteristics and health‐related outcomes of patients with HS‐detected AF may differ from those of patients whose AF was detected by other procedures. Methods: In total, 3318 consecutive newly referred AF cases were enrolled; demographic characteristics and health‐related and clinical outcomes were compared between two groups created based on the mode of AF detection (the HS and non‐HS groups). Health‐related outcomes were assessed using the AF Effect on QualiTy‐of‐life (AFEQT) questionnaire at baseline and after 1 year of follow‐up. Results: AF was detected by HS in 25.0% of patients; these patients had lower CHADS2 scores (1.01 vs. 1.50, p  < .001), higher prevalence of persistent AF (odds ratio, 95% confidence interval; 2.21, 1.88–2.60) and asymptomatic presentation (3.19, 2.71–3.76), and better baseline QoL scores (83.6 vs. 75.0; p  < .001). Catheter ablation was more frequently performed in the HS group at follow‐up (44.4% vs. 34.1%; p  < .001). At 1‐year follow‐up, the AFEQT scores of the HS group were significantly better in most subdomains. Conclusions: In the Japanese registry, AF was detected via HS in 25% of patients referred to specialty centers for management. Notably, the overall health status of patients with HS‐detected AF improved after medical interventions, including catheter ablations.